Assessing Ecological Resilience of Eastern Indonesian Coral Reefs - Bahtiar, Imam; Damar, Ario; _, Suharsono; Zamani, Neviaty P (Journal of Indonesian Coral Reefs, 2011)
Eastern Indonesian reefs are located on the CTI region, that understanding their ecological resiliencies are therefore very important for management of the region. Coral reef resilience was assessed using a resilience index on the 2009 Coremap data. Resilience index used in the assessment was developed by the author but published elsewhere. The study included 7 districts in eastern Indonesia: Pangkep (Pangkajene Kepulauan), Selayar, Buton, Wakatobi, Sikka, Raja Ampat and Biak. The results showed that coral reefs at Wakatobi had the highest average resilience indices, while Sikka had the lowest one. High resilience index at Wakatobi coincided with high number of coral functional groups (life forms) and coral cover. Low average resilience index at Sikka coincided with high algae and other fauna covers. Raja Ampat had coral reefs with a fair resilience index which is similar to coral reefs at Pangkep and Selayar.